CRISPR-Cas13a-powered electrochemical biosensors for RNA-based disease diagnostic and monitoring - Salma Nur Zakiyyah; Irkham; Karina Salsabiila Putri Sima; Clianta Yudin Kharismasari; Mengzhen Xi; Shabarni Gaffar; Mehmet Ozsoz; Francesco Paolucci; Giovanni Valenti; Yeni Wahyuni Hartati (Sensors and Actuators Reports, 2025)
Nucleic acids serve as specific, selective, and sensitive components in molecular diagnostics, offering efficient and high-precision results. Unlike DNA, RNA expression reflects real-time cellular activity, allowing for the monitoring of disease progression, treatment response, or environmental influences. This makes RNA a superior biomarker due to its ability to enable early disease detection, provide higher specificity, allow non-invasive sampling, and offer high sensitivity for low-abundance targets. RNA-based biosensor innovations hold significant potential for detecting genetic diseases, such as cancer, and preventing viral infections. Electrochemical biosensors have become a fast and efficient alternative to gold-standard diagnostic methods, offering simplicity, rapid response, and suitability for clinical use, including point-of-care applications. Recent advancements have integrated the CRISPR-Cas13a system with electrochemical biosensors to enhance RNA detection sensitivity and specificity. The CRISPR-Cas system, an adaptive immune mechanism in bacteria, has been widely utilized for diagnostics. Cas13a is superior to other Cas proteins for RNA detection due to its high specificity, inherent signal amplification, and ability to detect low-abundance RNA without requiring reverse transcription or amplification steps. This review summarized recent progression of CRISPR/Cas 13a and its combination with electrochemical technique, including electrochemiluminescence (ECL) and photoelectrochemical (PEC) methods. The principles and advantages of CRISPR/Cas13a, electrochemical, ECL, and PEC technique for RNA detection are described. In electrochemical-based biosensors, Cas13a recognizes and binds to the target ssRNA, triggering its trans-cleavage activity, which indiscriminately cuts nearby RNA reporters. This process alters the electrochemical signal, enabling selective and sensitive RNA detection. Finally, several examples of CRISPR/Cas13a-based electrochemical biosensors are discussed, highlighting their potential as molecular diagnostic tools for RNA detection and emphasizing their advantages in sensitivity, specificity, and rapid detection capabilities.© 2012 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of Global Science and Technology Forum Pte Ltd